CONNECTIONS BETWEEN ART, SCIENCE AND EDUCATION: EXPERIENCING THE CONCEPT IMAGINARY MUSEUM (Palíndromo, 2019)
The concept of Malraux's imaginary museum (2006) invites us to experience relationships between scientific and ar-tistic languages, in different learning contexts. The dialogues between artistic practices and scientific procedures lead us to ask: Can any place become a learn-ing context? The relationship we have es-tablished with contemporary art allows us to imagine other forms of learning; this relationship allows us to make unexpect-ed connections with unlikely situations, because in any context we can generate learning. The projects generated from in-ter and transdisciplinarity are becoming through different forms of knowledge, they are procedures that establish bridg-es between the content to be taught and the context lived. These practices expe-rience new cultural mediation strategies through artistic processes, showing fu-ture teachers different possibilities with the purpose of expanding their cultural repertoire as well as the construction of meanings that allow them different inter-pretations of the school and the world.
Keywords: imaginary museum; education; art; science